Pulse Current Gas Metal Arc Welding Characteristics, Control and Applications - Ghosh, Prakriti Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This monograph is a first-of-its-kind compilation on high deposition pulse current GMAW process. The nine chapters of this monograph may serve as a comprehensive knowledge tool to use advanced welding engineering in prospective applications. The contents of this book will prove useful to the shop floor welding engineer in handling this otherwise critical welding process with confidence. It will also serve to inspire researchers to think critically on more versatile applications of the unique nature of pulse current in GMAW process to develop cutting edge welding technology.
Introduction to Gas Metal Arc Welding -- Concept of Pulse Current Gas Metal Arc Welding Process -- Basic Nature of Pulse Current GMA Welding -- Thermal Behaviour of Pulse Current Gas Metal Arc Weld -- Geometry of Pulse Current GMA Weld -- Characteristics of P-GMA Weld Joint -- Properties of Pulse Current GMA Weld -- Prospective Use of Pulse Current GMAW Process -- Advanced Power Source and Process Control.
Keywords: Manufactures; Machinery; Coatings; Tribology; Corrosion and anti-corrosives.; Machines, Tools, Processes; Machinery and Machine Elements; Coatings; Tribology; Corrosion